(untitled) (Journal of Hama University, 2021)
The study aimed to detect the content of broiler liver from the antibiotics Doxycycline and Enrofloxacin, and to compare results with the maximum residue limits (MRLs) allowed locally and internationally, to assess the safety and validity of its human consumption. 96 random samples of broiler liver were collected from the markets of Latakia during 2018, and they were extracted and analyzed on HPLC device using high-performance liquid chromatography technology in the laboratories of the Ministry of Agriculture in Damascus. The results showed an increase in Doxycycline levels (278.11- 2008.01 µg/ kg), and 87.5% of the samples was positive for its presence, and 83.3% of the total samples exceeded the MRL in broiler livers. The results also showed an increase in the Enrofloxacin levels (86.67-308.48 µg/ kg), and 91.67% of the samples showed positive results, and 45.8% of the total samples exceeded the MRL in broiler livers. This necessitates strict control over the content of antibiotics in broiler carcasses. Statistical analysis of the Doxycycline results showed significant differences P≤0.05 when comparing its mean concentration in the third quarter with the mean of other quarters, and for Enrofloxacin when comparing its mean concentration in the second quarter samples with the mean of other quarters.